Beyond EUI - Keith Peiffer; Khaled Mansy; Christina McCoy; Jay Yowell (Building Technology Educators’ Society, 2025)
This paper will discuss the relationship between design-assisting tools and the resulting methodology for detailed assessment of building performance in the design studio. In doing so, we hope to provide insight for educators seeking to leverage the use of similar tools within the design studio. By maximizing impact on student learning, we can help our students shape their future careers to face the significant challenges posed by climate change.
Keywords: EUI; design tools; building performance